DESKRIPSI KEPUASAN MAHASISWA TERKAIT PELAYANAN PENGURUS LK CHANNEL - Dasia Mayangsari; Fadil Bahar; Muhajir; Muh Sahid; UMAIRAH, JIHAN PUTRI (Journal of Media and Communication Studies, 2023)
Every student certainly wants to achieve the goals he has set, and to achieve these goals, our role as humans involved in them is very important. Students of the Islamic Communication & Broadcasting Study program as subjects for this research. Of course this research provides service and satisfaction for students, of course they also want to achieve the goals that have been set. Quality service plays an important role in shaping satisfaction for KPI 2021 class students. So the better the service provided by the LK channel administrators, the higher the level of satisfaction for KPI 2021 class students. The indicators used in this study are Reliability, Assurance, Responsiveness, Empathy, and Direct Evidence. In this indicator we can provide instructions or information. This indicator can also be a reference in achieving a goal. Indicators can be used to determine the factors of change in achieving these goals. the number of students will cause a lot of dynamics in viewing the management of the LK channel management towards the facilities provided. At the same time, students also expect to be given the best service in their various dealings with the LK channel management.Based on the background above, the general problem formulation in this study is how the 2021 KPI student satisfaction forms with the services of LK channel administrators.